Effects of livestock and wildlife grazing intensity on soil carbon dioxide flux in the savanna grassland of Kenya - Wachiye, S.; Pellikka, P.; Rinne, J.; Heiskanen, J.; Abwanda, Sheila O.; Merbold, Lutz (Elsevier, 2022)
Although grazing is the primary land use in the savanna lowland of southern Kenya, the effects of grazing on soil carbon dioxide flux (RS) remain unclear. A 12-month study was conducted from January to December 2020 on the effects of six grazing intensities sites (overgrazed (OG), heavily grazed (HG), moderately grazed (MG), moderately to lightly grazed (M-LG), lightly grazed (LG) and no grazing (NG)) on RS on. A camera trap was used to monitor the total number of animals at each site, indicating the grazing intensity. Weekly measurements of RS were taken using static greenhouse gas chambers along with simultaneous measurements of soil temperature (TS) and volumetric soil water content (WS) (depth of 5 cm). Mean RS at HG, MG, M-LG and LG sites was approximately 15–25% higher than at NG and OG sites (p < 0.001). Mean WS increased with decrease in grazing especially in the dry season, while TS increased with increase in grazing. We observed bimodal temporal variation in RS and WS due to two wet seasons in the year. Thus, variation in RS across the study period followed the changes in WS rather than those in TS. Mean values of RS in the wet seasons were significantly higher (> 45%) than those in the dry seasons, and WS accounted for 71% of the temporal variability in RS (p < 0.05). In addition, the enhanced vegetation index (EVI, interpreted as a proxy for vegetation cover) explained 60% of the variance of RS, and WS and EVI together explained 75%. EVI showed a negative relationship (p < 0.05) with animal intensity, indicating that more grazing reduced vegetation cover and, consequently, soil organic carbon and biomass. Soil bulk density was lower at less grazed sites. While RS variability was unaffected by total nitrogen content, pH, and texture, correspondence analysis demonstrated that the main factors influencing RS dynamics across the year under different grazing intensities were WS and vegetation cover. Our results contribute to closing the existing knowledge gap regarding the effects of grazing intensity on RS in East Africa savannas. Therefore, this information is of great importance in understanding carbon cycling in savanna grassland, as well as the identification of the potential consequences of increasing land pressure caused by rising livestock numbers, and will assist in the development of climate-smart livestock management in East Africa.